Experimental analysis of dual-rotor-support-casing system with blade-casing rubbing. (May 2021) - Wang, Nanfei; Liu, Chao; Jiang, Dongxiang
Graphical abstract: Highlights: Improved contact model for rubbing between blade and casing and comparisons. vibration features of inner rotor and casing under blade-casing rubbing. Experiments on blade-casing rubbing and verifications with numerical simulations. Abstract: Vibration features of inner rotor and casing of a dual-rotor-support-casing (DRSC) system with rubbing existing between blade and casing are analyzed in this work. First, an improved model for analyzing rubbing between blade and casing is presented, in which the kinetic energy of the blade, the deformations of blade and casing are considered. Second, a finite element model of the DRSC system is built as well as the motion equations, where unbalance and time-varying pulse load is considered. Third, natural frequencies and modes, acceleration responses of the casing, and inner rotor of the system with blade-casing rubbing faults are obtained. Finally, the blade-casing rubbing experiments are implemented on the dual-rotor-support-casing test rig, compared with dynamics analysis. The results indicate that (i) the improved rubbing model is more accurate in describing the impact of rubbing between blade and casing; and (ii) the components of impact frequency and the coupling frequencies are prominent when blade-casing rubbing occurs and validated by the experimental results.